PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. DAMASES SEJAHTERA - Irawati, Anastasia; Budiwinarto, Kim (Surakarta Management Journal, 2022)
This research is intended to determine the effect of leadership and work environment on employee performance at PT. Damases Sejahtera both partially and simultaneously. This research was a quantitative case study. Secondary data obtained from the data collected by using the questionnaire with the number of samples of 108 respondents. The results showed partially (t-test statistically) all leadership variables and work environment positive and significant to the employee performance at PT. Damases Sejahtera. The results showed simultaneously (F-test statistically) leadership and work environment significantly to the employee performance at PT. Damases Sejahtera.